Študijsko gradivo pri predmetu Gospodarsko in statusno pravo: izbrane teme: Zbirka vaj - Jerneja Prostor, Jerneja Prostor; Burkelc Juras , Lina (University of Maribor Press, 2023)
Study Material for the Course Business and Company Law: Select topics: Collection of Exercises. This study material provides a starting point for preparation for the course Corporate status law: Select topics of 2nd degree Bologna study. The goal of the course is to gain integrated knowledge of different fields of Corporate Law and Company Law, which is later useful for the preparation for the Slovenian Bar Exam. This study material therefore helps the students to first repeat their theoretical knowledge of certain topics and then further elaborate on that knowledge by solving some practical cases, which enable them to examine, whether they understood the lectures and theory correctly. When solving the questions and practical cases in this study material, students are expected to use the Slovenian Companies Act (ZGD-1), Financial Operations, Insolvency Proceedings, and Compulsory Dissolution Act (ZFPPIPP), Register of Companies Act (ZSReg), Obligations Code (OZ), Prevention of Restriction of Competition Act (ZPOmK-2), Takeovers Act (ZPre-1), Industrial Property Act (ZIL-1), Copyright and Related Rights Act (ZASP), Institutes Act (ZZ), Cooperatives Act (ZZad), and others. In addition, students should also study the relevant court practice. Study material includes questions from the following fields: Fundamentals of Company Law, Affiliated Companies, Dissolution of a Company, Court Register, Commercial Contracts, Intellectual Property Law, Competition Law and Changes of Companies Legal Status.